Methodologies for estimating shipping emissions and energy consumption: A comparative analysis of current methods. (15th June 2015) - Moreno-Gutiérrez, Juan; Calderay, Fátima; Saborido, Nieves; Boile, Maria; Rodríguez Valero, Rafael; Durán-Grados, Vanesa
Abstract: The debate on the evaluation of maritime emissions offers several different methods of estimating emissions. These methods are not easily compared due to their analysis of different contexts and their underlying different assumptions. The estimates of the International Maritime Organization in confirmed some of the results in the literature, but the debate is ongoing. In this manuscript, factors from nine methods that have been applied for the evaluation of fuel consumption and emissions are studied and compared. The review and application of these maritime emission inventories reveal no significant differences between these methods. Regarding the total pollutant values, the largest differences correspond to the application of the factors employed by the International Maritime Organization for main engines, and the smallest differences correspond to the application of the factors employed by the Environmental International Corporation for auxiliary engines. The recommendations made in this manuscript include the use of the STEAM (ship traffic emission assessment model) method, the use of the method developed by Goldsworthy to apply the emission factors and the consideration of the maintenance state of the engines as an additional uncertainty factor. The analysis made in this manuscript shows more possibly detailed methods that can substantially improve the quality of bottom–up inventory estimates. Highlights: Ship's energy and emission inventories are subjected to high uncertainties. Nine energy and emission inventory methods have been studied and compared. The engine's maintenance should be introduced as an uncertainty factor. The tests on board is the best method for the calculation of emission.